Yes job (Web site for job opportunities between job seekers and employers using MVC) - Hafiz Naim, Mahazan (2018)
YES JOB is a system where it operates employers and job seekers in Malaysia. It is a webbased system, where users need access to this system by using internet access. YES JOB has been developed because of the specific problems faced by employers and job seekers. The problem is, jobseekers find it difficult to find jobs that are appropriate for them and employers need a long time to find employees. The objective of YES JOB is to review existing websites to develop systems that can facilitate employers and job searchers. The YES JOB system has been developed using the Rapid Application Rapid (RAD) method. This methodology is chosen because in order to develop YES JOB, it requires cooperation from employers and job seekers for their feedback. using this methodology as well, can accelerate the development process. To ensure that YES JOB works properly the test should be performed on this system. The YES JOB system focuses on black box testing. It is because the black box test only tests the system based on its function and needs. This system has several functions, where this system will manage the employer's information, manage job seekers information and others.